Ritual Mistis di Dunia Politik: Studi pada Ritual Ngalab Berkah di Gunung Kemukus - Nugroho, Fibry Jati (Hanifiya: Jurnal Studi Agama-Agama, 2020)
Mystical rituals are still very thick in people's lives. Even though the times are modern, rituals in the supernatural are still performed. Community life cannot be separated from mystical rituals, which are then manifested in their spiritual practice. In this study presented a mystical ritual performed by pilgrims who Ngalab Berkah on Gunung Kemukus. Theritual Ngalab Berkah will be used as an object of study in relation to contestation in the political world. By using a qualitative approach and descriptive analysis, it was found that theframe Javanese religious and Max Weber's theory regarding charismatic leadership caused mystical rituals to remain in demand among political contestants. The results of mystical rituals in the form of Ngalab Berkah on Gunung Kemukus, make ritual performers get harmonization between macrocosm and microcosms, charisma as a leader, get pulung (kebegjan), and get wisdom and mercy from Prince Samudra. Mystical rituals carried out by pilgrims proved to be a powerful enough path for political contestants to win their contest in the political world.